TINDAK TUTUR EKSPRESIF DALAM FILM ANIMASI UPIN DAN IPIN SIARAN TELEVISI SWASTA MNCTV (KAJIAN PRAGMATIK) - Elan Halid (Asosiasi dosen IDEBAHASA KEPRI, 2021)
The problem to be discussed in this research is how the expressive speech acts in the animated film Upin and Ipin are broadcast on MNCTV private television. Pragmatics is the study of all aspects of meaning that have been covered in semantic theory, or in other words: discussing all aspects of the meaning of speech that cannot be explained completely by direct reference to the conditions of truth of the sentence spoken. Speech acts are actions that are displayed through utterances to convey one's intentions and goals to others in life situations. Expressive is a type of speech act that states something the speaker feels. Animated films are films that are the result of processing hand drawings, so that they become moving images. Animated films are basically based on fantasy stories. While the source of data in the research is the animated film Upin and Ipin. This type of research is a qualitative research with descriptive method. After the researchers conducted research and grouped the results of the research data based on expressive speech acts, the researchers obtained 27 data. The speech act of thanking found 5 data, apologizing found 4 data, congratulating found 3 data, praising found 5 data, complaining found 6 data, and blaming found 4 data. The conclusion in this study is that expressive speech acts in the form of complaining are the most commonly found in the animated film Upin and Ipin.